2018
DOI: 10.12973/iji.2018.11227a
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Critical Thinking Skills in Chemistry Learning Using Local Culture-Based 7E Learning Cycle Model

Abstract: This research aimed at describing the effectiveness of the local culture-based 7E learning cycle model in improving students' critical thinking skills in chemistry learning. It was an experimental research with post-test only control group design. The population was the eleventh-grade students of senior high schools in Singaraja, Indonesia. The sample included 111 students; 57 students as the experimental group and 54 students as the control group. The students in the experimental group learned through the loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
14

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 15 publications
(11 reference statements)
3
63
0
14
Order By: Relevance
“…In the 21st century, the development of science, technology, and information takes place very quickly and is full of competition. To anticipate and win this competition, Indonesi-ans must prepare themselves by growing and developing many competencies (Suardana et al, 2018). Thus, it brings the impact of a tight race in all areas of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 21st century, the development of science, technology, and information takes place very quickly and is full of competition. To anticipate and win this competition, Indonesi-ans must prepare themselves by growing and developing many competencies (Suardana et al, 2018). Thus, it brings the impact of a tight race in all areas of life.…”
Section: Introductionmentioning
confidence: 99%
“…The conservation knowledge lives in the community were dug up to be translated into conservation materials and included in the worksheets. The examples of indigenous knowledge included the terasering technique applied by Balinese people (Suardana et al, 2018) or preservation of Mangrove and National Park by Karimunjawa residents (Dewi et al, 2019). Moreover, the use of the ethnoscience approach has been proven to be able to develop thinking skills (Setiawan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The reasons underlied this rational description are the instructional model cognitive strategies based involved interactive components which consist of :assessing higher order thinking abilities of the students before participating the cognitive strategies based instructional approach , deciding instructional goals, deciding students' learning achievement, deciding instructional strategies, deciding instructional materials, deciding instructional evaluation , and deciding instructional feed back as shown in figure 2. All of them are the reflection of synthesized of the theories and research results which have been described previously.The research finding dealing with the intructional model which involves interactive componens are also supported by Suardana [48] and Wei Fang [49] VI. CONCLUSION In accordance to the research results, it is concluded that cognitive strategies based instructional model is effective for improving higher order thinking of the students with cognitive expressing difficulties.…”
Section: Discussionmentioning
confidence: 66%
“…Hudgin [23] described that critical thinking is a form of higher order thinking which constructed based on the understanding of problems or statements, as well as, empirical facts. All of them can be identified from: exploring any related facts which supported by any statements or any summaries, evaluating any statements, in order, to get to know relation or different among them, evaluating inductive process based policies, evaluating the conformation of the relation between statements and theories, evaluating the back ground underlined any circumstances which cause any problems [24].…”
Section: Introductionmentioning
confidence: 99%
“…By knowing the problems of teaching, it will be formulated appropriate learning strategies to overcome these chemistry teaching problems encountered. Several learning strategies have been developed to address the teaching problems related to the conceptual change model, including (a) the conceptual change texts [5] [18] [19] [20], (b) analogies [21], (c) the holistic mental model confrontation [22], (d) the web-based conceptual change texts [23], (e) the computer simulations [24], (f) the computer-based learning [25], and local culture-based 7E learning cycle model [26]. In preparing this conceptual change learning strategy, the teachers should also pay attention to the students' learning style [27].…”
Section: Resultsmentioning
confidence: 99%